Ultrasonography of the neotropical primate female reproductive system - Domingues, Sheyla Farhayldes Souza; Leão, Danuza Leite; Monteiro, Frederico Ozanan Barros (Frontiers in Veterinary Science, 2024)
The Neotropical (e.g., Aotus sp., Callithrix jacchus, Saguinus sp., Saimiri sp., and Sapajus sp.) primates are important models for biomedical research and studies on reproductive physiology and biotechnology. Consequently, studies about gynecological and obstetric ultrasonography are crucial.B-mode ultrasonography is a noninvasive imaging technique that provides real-time bidimensional or three-dimensional/four-dimensional B-mode images. In association with Doppler ultrasonography, B-mode ultrasonography can also be used to monitor the mammalian blood flow to the reproductive tract during important events such as ovulation and gestation. Thus, gynecological and obstetric ultrasonography is essential for establishing the female reproductive anatomical and physiological ovarian and uterine health status, gestational diagnosis, and fetal growth monitoring. For instance, the paper presents and discusses the state-of-the-art gynecological and obstetric ultrasonography in the Neotropical primates, species that are models for biomedical research, and some recent studies on species targets for conservation strategies for wild animal populations.